NGHIÊN CỨU ĐA DẠNG SINH HỌC NẤM MEN NỘI SINH PHÂN LẬP TRÊN CHUỐI TIÊU HỒNG Musa sapientum L. TẠI KHU VỰC GIA LÂM, HÀ NỘI - Chu, Thanh Bình; Đỗ, Thị Thu Hồng; Ngô, Cao Cường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON BIODIVERSITY OF ENDOPHYTICYEAST ISOLATED IN BANANAS Musa sapientum L. IN GIALAM DISTRIST, HANOI20 endophytic yeast strains are isolated from 41 samples of flower, young fruit, old fruit of bananas Musa sapientum L.. The strains are divided into 16 groups based on morphological characteristics. The number of the endophytic yeast having cellulase, protease and amylase activity is 16, 15 and 6 respectively. When the endophytic yeast strains are studied by fingerprinting, they belong to 15 groups with high reliability.